Telengana movement : 1944-51 - Pavier, Barry (New Delhi, 1981)
This book has had an unusual history. It started life as a D. Phil. project for the University of Sussex and it was during that period that I spent a year, 1973-74, researching in India, thanks to a grant from the Social Science Research Council. It was never written as a thesis as I found myself unable to deal with the unspoken demands on research students in this field to make some kind of definitive statement on the major debates in their theses. This asks rather too much of people engaged in producing what is after all only their first monograph. Many academics of position if not repute go through their entire careers without attempting any such definitive statement and I found the demands seriously inhibited my ability to come to terms with the topic on a less elevated basis.
Keywords: Andhra Pradesh social conditions